2020
DOI: 10.1002/lary.28936
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐institutional Survey of Squamous Cell Carcinoma of the External Auditory Canal in Japan

Abstract: Objectives This study aimed to evaluate the efficacy of chemoradiotherapy (CRT) for patients with advanced cancer of the external auditory canal (EAC) by analyzing the outcome of the patients. Methods This is a multi‐institutional retrospective survey, and we reviewed the medical records of the subjects. A total of 181 patients with tumor (T)3 or T4 tumor in 17 institutions were enrolled. Further analysis was performed for 74 patients who underwent CRT under curative intent. Results Overall 5‐year survival rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 18 publications
1
15
0
Order By: Relevance
“…TPF as an induction chemotherapy was shown to achieve significantly better survival than cisplatin and fluorouracil in unresectable head and neck cancer (22,23). Shiga et al reported that the overall 5-year survival rates of patients with T3 or T4 EAC carcinoma who underwent CCRT with TPF and cisplatin regimens were 64.4 and 36.7%, respectively (21). These reports demonstrate that CCRT with TPF is a promising therapy for advanced EAC carcinoma, which is unfit for STBR.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…TPF as an induction chemotherapy was shown to achieve significantly better survival than cisplatin and fluorouracil in unresectable head and neck cancer (22,23). Shiga et al reported that the overall 5-year survival rates of patients with T3 or T4 EAC carcinoma who underwent CCRT with TPF and cisplatin regimens were 64.4 and 36.7%, respectively (21). These reports demonstrate that CCRT with TPF is a promising therapy for advanced EAC carcinoma, which is unfit for STBR.…”
Section: Discussionmentioning
confidence: 97%
“…In this study, a cisplatin-based regimen was mainly used for CCRT, according to the standard therapy for head and neck carcinoma. As an alternative to cisplatin-based regimens, the TPF regimen (docetaxel, cisplatin, and fluorouracil), which enhances the intensity of CCRT (19)(20)(21), may be considered for the management of unresectable T3/T4 tumors. TPF as an induction chemotherapy was shown to achieve significantly better survival than cisplatin and fluorouracil in unresectable head and neck cancer (22,23).…”
Section: Discussionmentioning
confidence: 99%
“…Shiga et al showed that T4‐classified tumors were treated primary with chemoradiotherapy when the tumor involves the cochlear, jugular foramen, dura mater invasion, or brain invasion 30 . Results of other studies also presented beneficial effects of chemoradiotherapy on survival outcomes of EAC SCC, but all studies used different chemoradiation protocols and the sample sizes were too small for meaningful evaluation 31–38 …”
Section: Discussionmentioning
confidence: 99%
“…30 Results of other studies also presented beneficial effects of chemoradiotherapy on survival outcomes of EAC SCC, but all studies used different chemoradiation protocols and the sample sizes were too small for meaningful evaluation. [31][32][33][34][35][36][37][38] 4.6 | Alternative T4-subclassification Shinomiya et al suggested in 2021 another subclass for T4-classified EAC SCC consisting of T4a-subclass including T4-classified tumors without involving the brain, internal carotid artery, and internal jugular vein and of T4b-subclass including T4-classified tumors that involve one of these three previous mentioned structures. 39 Their T4a-class is comparable to the T4a-class and T4b-class of Lavieille et al and their T4b-class is comparable to the T4c-class of Lavieille et al It would be interesting to evaluate the DFS and OS of these two subclasses to evaluate and compare the clinical added value of both systems.…”
Section: Chemoradiotherapymentioning
confidence: 99%
“…Neoplasms of the auditory organ are a rare disease with an annual incidence of (1-6/1000000) for SCC [19][20]. Surgery is the major initial therapy for patients with cancer of the external auditory canal, however, it is controversial because expert techniques are needed for rarity and the complex anatomy of the temporal bone including cranial nerves, internal carotid artery, and brain.…”
Section: Auditory Organ Cancermentioning
confidence: 99%